2003
DOI: 10.1046/j.1439-0434.2003.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Swiss Needle Cast Disease: Temporal and Spatial Investigations of Fungal Colonization and Symptom Severity

Abstract: Increasing severity of Swiss needle cast (SNC), a foliar disease of Douglas‐fir caused by the fungus Phaeocryptopus gaeumannii, has become a matter of concern in forest plantations throughout coastal Oregon and Washington. This study monitored SNC disease in three Oregon Douglas‐fir plantations bi‐annually in 1998–1999, and compared differences in fungal colonization and symptom development in trees from north‐ and south‐facing plots at each plantation. Fungal colonization as quantified by ergosterol content, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…However, foliage litterfall decreased as aspect became more northeasterly despite an expectation of lower water stress and more rapid growth. In this study, however, aspect is confounded with SNC severity as indicated by higher fungal colonization and more severe SNC symptoms reported by Manter et al [40] for south slopes.…”
Section: Amountmentioning
confidence: 69%
See 2 more Smart Citations
“…However, foliage litterfall decreased as aspect became more northeasterly despite an expectation of lower water stress and more rapid growth. In this study, however, aspect is confounded with SNC severity as indicated by higher fungal colonization and more severe SNC symptoms reported by Manter et al [40] for south slopes.…”
Section: Amountmentioning
confidence: 69%
“…Litterfall SLA increased as plots became steeper and more southerly (p < 0.0001), while it decreased with distance from the coast (p < 0.0001). SNC severity and its interaction with distance from the coast were not significant, most likely because SNC severity has been shown to increase on southern aspects [40] and decrease with distance from the coast [50]; hence, the marginal effect of SNC was not significant. Litterfall SLA changes systematically with Julian date (p = 0.0002), with a minimum in late March/early April and a maximum in December.…”
Section: Litter Specific Leaf Areamentioning
confidence: 92%
See 1 more Smart Citation
“…Later studies of SNC disease physiology revealed that these symptoms are caused by reduced gas exchange in the needles due to the occlusion of the stomata by ascocarps (pseudothecia) produced by this fungus. This blockage of the stomata leads to a reduction in carbon assimilation proportional to the percentage of total stomates occupied by pseudothecia [3] Abscission occurs when a needle ceases to function as a carbon source [4]. Regional SNC aerial surveys conducted annually since 1996 have documented gradual expansions in the area affected by the disease and in…”
Section: Introductionmentioning
confidence: 99%
“…Manter et al (2003) also noted that plots with southern exposures, which received greater amounts of solar radiation, had greater amounts of needle abscission compared to northaspect plots with similar amounts of P. gaeumannii colonization. Any influence of aspect on severity of Dothistroma infection has yet to be documented.…”
Section: Topographymentioning
confidence: 81%